2016
DOI: 10.18869/acadpub.aassjournal.4.3.27
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Brand Image and Brand Trust in Sporting Goods Consumers

Abstract: The image of a brand is the first word or image that is evoked in the mind of costumers immediately after hearing the brand name. The purpose of paying attention to the brand image is to ensure the proper mentality of consumers toward the brand. The components such as suitability, services, brand, variety, quality, and atmosphere form the brand image. The relationship between the brand image and other fields such as brand trust has been considered by researches and can play an effective role in improving the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 12 publications
2
18
0
8
Order By: Relevance
“…Salah satu tujuan dari experiential marketing adalah meningkatkan citra merek perusahaan. Saat ini, citra merek suatu perusahaan adalah salah satu aset terpenting yang tidak hanya membentuk keunggulan kompetitif, tetapi juga membantu perusahaan tetap berada di benak pelanggannya dan menghasilkan loyalitas pelanggan kepada perusahaan (Deheshti et al, 2016). Saat ini, konsep experiential marketing telah diperkenalkan secara luas ke banyak industri, seperti olahraga, rekreasi, dan pariwisata (Cuellar et al, 2015), restoran (Pratminingsih et al, 2018), bisnis ritel (Rosadi et al, 2019), maskapai penerbangan (Alagoz & Ekici, 2014), layanan medis (Gheorghe et al, 2017), dan kedai kopi (Chang, 2020).…”
Section: Pendahuluanunclassified
“…Salah satu tujuan dari experiential marketing adalah meningkatkan citra merek perusahaan. Saat ini, citra merek suatu perusahaan adalah salah satu aset terpenting yang tidak hanya membentuk keunggulan kompetitif, tetapi juga membantu perusahaan tetap berada di benak pelanggannya dan menghasilkan loyalitas pelanggan kepada perusahaan (Deheshti et al, 2016). Saat ini, konsep experiential marketing telah diperkenalkan secara luas ke banyak industri, seperti olahraga, rekreasi, dan pariwisata (Cuellar et al, 2015), restoran (Pratminingsih et al, 2018), bisnis ritel (Rosadi et al, 2019), maskapai penerbangan (Alagoz & Ekici, 2014), layanan medis (Gheorghe et al, 2017), dan kedai kopi (Chang, 2020).…”
Section: Pendahuluanunclassified
“…Carter (2010) defined a personal brand as a brand, a set of individuals' perceptions of a particular person and what differs in one person from others in his personality, fame, and character. He stated that athlete's life story, values, charisma, credibility, acceptance, and success all influence the athlete's position in the audience's mind (8). Rampersad and Hubert (2008) believed that a personal brand is more than the power of influencing sales and marketing in a competitive setting.…”
Section: Introductionmentioning
confidence: 99%
“…Tracey (2014) identified some of the obvious constraints on corporate reputation; among these is the confusion and contradiction in the concept of reputation and its close relationship with some of other subjects, including the brand image and identity (14). The brand identity is the image of a brand that a company wants to possess, which is the ideal image of a favorable brand (15). The starting point of the corporate reputation is the corporate identity which reflects a company's characteristics which are in turn reflected in the domestic culture and corporate values.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of focusing on the brand image is to ensure that consumers have a proper attitude towards the brand. Researchers believe that the higher level of brand reputation is more likely to lead to a higher satisfaction level and brand loyalty (15). The findings of Courtright and Smudde (2009) indicated that there is a relationship between the public relations and message content and the brand identity and image to enhance the organizational reputation.…”
Section: Introductionmentioning
confidence: 99%